Individual Specialization in the Hunting-wasp Trypoxylon (Trypargilum) agamemnon Richards (Hymenoptera: Crabronidae) - Pitilin, Renan B.; Araujo, Marcio S. [UNESP]; Buschini, Maria L. T. (Acad Sinica Inst Zoology, 2012)
Renan B. Pitilin, Marcio S. Araujo, and Maria L.T. Buschini (2012) Individual specialization in the hunting-wasp Trypoxylon (Trypargilum) agamemnon Richards (Hymenoptera: Crabronidae). Zoological Studies 51(5): 655-662. Individuals of a population may differ with respect to resource use. This among-individual variation in resource utilization is called 'individual specialization' and may substantially impact the ecological and evolutionary dynamics of a population. The aim of this study was to evaluate whether females of 1 population of the hunting-wasp Trypoxylon agamemnon differed in their preferences for spider size and/or taxa. To observe the behavior of wasps, trap-nests were installed in an araucaria forest fragment in the Parque Municipal das Araucarias, Guarapuava (PR), southern Brazil. The indices within-individual component (WIC)/total niche width of a population (TNW) and average of values of the proportional similarity index (IS) were used to measure the degree of individual specialization. We found evidence of strong, significant individual specialization in T agamemnon in terms of both prey size (WIC/TNW = 0.43) and taxa (IS = 0.45). We hypothesized that individual specialization in this species resulted from cognitive tradeoffs that limit individuals to exploring a small subset of available resources. http://zoolstud.sinica.edu.tw/Journals/51.5/655.pdf
Keywords: Anyphaenidae; Apoidea; Cognitive tradeoffs; Intra-population variation; Niche variation